Enhancing Speaking Skills By Using Focus Group Discussion (FGD) Technique to Eighth Grade Student of SMP Swasta Budi Murni 2 Medan - sitohang, Mikhaela; Tarigan, Karisma Erikson; Pangaribuan, Jontra Jusat (English Lecturers and Teachers Association (ELTA), 2025)
This research was conducted to find out how Focus Group Discussion can improve the speaking ability of class VIII students with the research subjects as many as 60 students at SMP Budi Murni 2 Medan. This research was conducted using quasi-experimental method to compare the speaking ability of experimental class and control class using traditional method. The data was sourced from 30 eighth grade students, both from pre test, post test and questionnaire. The results showed a high appreciation of the improvement from before and after the application there was an increase in learning scores obtained by students. Before the implementation of FGD in the learning process students obtained an average score of 49.83. While after the implementation of FGDs students obtained an average score of 90.00. This shows that the implementation of FGDs is considered very appropriate for the English language learning process in class VIII students of SMP Swasta Budi Murni 2 Medan. Keywords : Focus Group Discussion, Speaking Skills